Cardiopulmonary exercise testing during follow-up after acute pulmonary embolism - Farmakis, Ioannis T.; Valerio, Luca; Barco, Stefano; Alsheimer, Eva; Ewert, Ralf; Giannakoulas, George; Hobohm, Lukas; Keller, Karsten; Mavromanoli, Anna C.; Rosenkranz, Stephan; Morris, Timothy A.; Konstantinides, Stavros V.; et al. (The European respiratory journal, 2023)
Background Cardiopulmonary exercise testing (CPET) may provide prognostically valuable information during follow-up after pulmonary embolism (PE). Our objective was to investigate the association of patterns and degree of exercise limitation, as assessed by CPET, with clinical, echocardiographic and laboratory abnormalities and quality of life (QoL) after PE. - Methods In a prospective cohort study of unselected consecutive all-comers with PE, survivors of the index acute event underwent 3- and 12-month follow-ups, including CPET. We defined cardiopulmonary limitation as ventilatory inefficiency or insufficient cardiocirculatory reserve. Deconditioning was defined as peak O2 uptake (V′O2) <80% with no other abnormality. - Results Overall, 396 patients were included. At 3 months, prevalence of cardiopulmonary limitation and deconditioning was 50.1% (34.7% mild/moderate; 15.4% severe) and 12.1%, respectively; at 12 months, it was 44.8% (29.1% mild/moderate; 15.7% severe) and 14.9%, respectively. Cardiopulmonary limitation and its severity were associated with age (OR per decade 2.05, 95% CI 1.65-2.55), history of chronic lung disease (OR 2.72, 95% CI 1.06-6.97), smoking (OR 5.87, 95% CI 2.44-14.15) and intermediate- or high-risk acute PE (OR 4.36, 95% CI 1.92-9.94). Severe cardiopulmonary limitation at 3 months was associated with the prospectively defined, combined clinical-haemodynamic end-point of “post-PE impairment” (OR 6.40, 95% CI 2.35-18.45) and with poor disease-specific and generic health-related QoL. - Conclusions Abnormal exercise capacity of cardiopulmonary origin is frequent after PE, being associated with clinical and haemodynamic impairment as well as long-term QoL reduction. CPET can be considered for selected patients with persisting symptoms after acute PE to identify candidates for closer follow-up and possible therapeutic interventions. - Tweetable abstract ERSpublications - click to tweetCardiopulmonary exercise limitation is frequent after PE and associated with persisting clinical, echocardiographic and laboratory abnormalities as well as worse QoL. CPET may serve as a diagnostic modality for patients with persisting symptoms after PE.